Agreement among Four Prevalence Metrics for Urogenital Schistosomiasis in the Eastern Region of Ghana. (18th December 2016) - Kosinski, Karen Claire; Kulinkina, Alexandra V.; Tybor, David; Osabutey, Dickson; Bosompem, Kwabena M.; Naumova, Elena N.
Abstract : Few studies assess agreement among Schistosoma haematobium eggs, measured hematuria, and self-reported metrics. We assessed agreement among four metrics at a single time point and analyzed the stability of infection across two time points with a single metric. We used data from the Eastern Region of Ghana and constructed logistic regression models. Girls reporting macrohematuria were 4.1 times more likely to have measured hematuria than girls not reporting macrohematuria (CI95% : 2.1–7.9); girls who swim were 3.6 times more likely to have measured hematuria than nonswimmers (CI95% : 1.6–7.9). For boys, neither self-reported metric was predictive. Girls with measured hematuria in 2010 were 3.3 times more likely to be positive in 2012 (CI95% : 1.01–10.5), but boys showed no association. Boys with measured hematuria in 2008 were 6.0 times more likely to have measured hematuria in 2009 (CI95% : 1.5–23.9) and those with eggs in urine in 2008 were 4.8 times more likely to have eggs in urine in 2009 (CI95% : 1.2–18.8). For girls, measured hematuria in 2008 predicted a positive test in 2009 (OR = 2.8; CI95% : 1.1–6.8), but egg status did not. Agreement between dipstick results and eggs suggests continued dipstick used is appropriate. Self-reported swimming should be further examined. For effective disease monitoring, we recommend annual dipstick testing.